2014
DOI: 10.1177/1029864914548912
|View full text |Cite
|
Sign up to set email alerts
|

Growing older in a symphony orchestra: The development of the age-related self-concept and the self-estimated performance of professional musicians in a lifespan perspective

Abstract: The use of the lifespan perspective as a reference point for analysing and researching the musical and artistic development of professional musicians has only recently begun to attract more attention amongst music researchers and educators and amongst musicians themselves. The knowledge about the processes of aging and their influences on making music is especially scarce. This study presents the results of a representative questionnaire on the issue of growing older in a symphony orchestra. A total of 2,536 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 24 publications
4
22
0
1
Order By: Relevance
“…The current study’s response rate was comparable with other studies (Fishbein et al, 1987; Gembris & Heye, 2014; Kenny et al, 2014), although the conclusions that can be drawn are limited by the absence of data for those musicians who chose not to participate. Furthermore, due to its cross-sectional nature, the current study was unable to provide information on the progression of flow and MPA across a lifetime of orchestral playing; longitudinal studies are necessary to provide this.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The current study’s response rate was comparable with other studies (Fishbein et al, 1987; Gembris & Heye, 2014; Kenny et al, 2014), although the conclusions that can be drawn are limited by the absence of data for those musicians who chose not to participate. Furthermore, due to its cross-sectional nature, the current study was unable to provide information on the progression of flow and MPA across a lifetime of orchestral playing; longitudinal studies are necessary to provide this.…”
Section: Discussionsupporting
confidence: 82%
“…The current study found no evidence of an association between MPA and age, although there was evidence of a positive association between age and flow not observed in other domains (Riva et al, 2017). It is possible that older players’ higher flow may help to “protect” them from increasing concerns about a deterioration in skills with age (Gembris & Haye, 2014) and account for evidence of increasing job satisfaction with age (Gembris et al, 2014, 2018). There is evidence that orchestral musicians enjoy their work (Brodsky, 2006; Smith, 1989), a higher proportion of musicians retain active careers beyond retirement age than in the non-musician population (Brodsky, 2011), and it appears that older musicians are valued in the orchestral workplace (Brandfonbrener, 2003; Smith, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the well-known gradual personality changes throughout life, where personality in older age becomes quite different from personality in childhood [60,61]. Although research into musical development in a lifespan perspective has been accumulating in the past decade or so [62,63], more specific research is required to conclude whether improvisational abilities and expressiveness change from younger to older ages, and if so—why. Here, we also suggest a changed characteristic.…”
Section: Discussionsupporting
confidence: 71%
“…In this article, the emphasis is put on the impact of physical therapy since epidemiology shows that the highest number of functional disorders in instrumentalists is from (neuro-) musculoskeletal (Fry, 1986;Fishbein and Middlestadt, 1988;Middlestadt and Fisbein, 1989;Brown, 1997;Dawson, 2002;Engquist et al, 2004;Bragge et al, 2005;Fjellman-Wiklund and Chesky, 2006;Abréu-Ramos and Micheo, 2007;Bruno et al, 2008;Hincapié et al, 2008;Ackermann et al, 2012;Gembris and Heye, 2014;Baadjou et al, 2016;Kok et al, 2016), a clinical field where physical therapists are acknowledged as skilled and autonomous practitioners for a long time (Chan et al, 2013a;.…”
Section: Introductionmentioning
confidence: 99%